Effects of Dried Leaves Extract of Spearmint (Mentha Spicata Labiateae) on Histology of Ovaries of Adult Female Wistar Albino Rats - Uzma Ali, Amber Salman, Humaira Gulnaz, Momna Riaz, Faiza Hanif, Shibrah Rafaqat (Pakistan Journal of Medical & Health Sciences, 2023)
Spearmin is a herb which has aromatic and medicinal properties. It is also used as flavoring agent in toothpaste, chewing gums, confectionaries and pharmaceutical preparation. The objective of this study was to evaluate the toxic effects of dried leaves extract of spearmint on gross and histological parameters of ovaries of adult female Wistar albino rats. Materials and Method: 60 female adult Wistar albino rats were taken in this study. After acclimatization rats divided into group A (Control), group B (Low dose experimental) and group C (High dose experimental) containing 20 rats each. Group A received distilled water whereas group B and C received dried leaves extract of spearmint in doses of 0.3 & 0.6 g / kg / day respectively, through gastric intubation for 30 days. Blood sampling and body weight of all the three groups were taken at the start & end of experiment. Ovaries of rats were dissected, observed for gross parameters and then prepared for histological examination. Result: All quantitative parameters had skewed distribution. The body weight of both experimental groups was decreased significantly (p – value < 0.001). Paired ovarian weight was increased significantly (p – value < 0.001). The ovaries of both experimental groups showed atrophied antral, Graffian follicles and corpora lutea significantly (p – value < 0.001). The decreased levels of serum progesterone were also observed. Conclusion: Use of spearmint in adult female rats showed significant harmful effects on morphology and histology of ovaries, hence it is recommended that further research work should be carried out to evaluate its other toxic effects on different organs of body Keywords: Spearmin, Graffian follicles, Ovary, Leaf extract